Relationship Between Wood Properties and Drying Qualities at Three Age Groups of Mindi (Melia azedarah L) Tree for Furnitur Materials - Saefudin, Saefudin; Basri, Efrida; Pari, Rohmah (Masyarakat Peneliti Kayu Indonesia, 2023)
All wood based products should have been dried to ensure their stable dimension. Indicators of stable dimension can be figured-out from wood physical properties, especially ratio of tangensial shrinkage to radial shrinkage (T/R ratio) and wood drying properties at high temperature. From those two indicators could be predicted the drying quality of wood as a basic to determine minimum – maximum of drying temperature. This research aimed to look-into the relationship between wood properties of wood and drying quality of mindi (Melia azedarach L)wood at their 5, 9, and 13 year-old trees. The preparing of test samples, and testing methods on wood physical properties covered moisture content, air-dry density, and shrinkage in tangential and radial direction, which referred to the BS 1957. Meanwhile, drying properties followed the modified Terazawa’s method. Five classes of wood drying qualities could be derived from the analysis of T/R ratio and drying property at each tree age group. Results revealed that wood density ranged about 0.46 – 0.58 g/cm3. Drying quality of each wood (except the portion near the pith) belong to B (good) for 13 years old, C (fair) for 9 years, and D (poor) for 5 years old. Related to the drying quality, the minimum – maximum temperature for 13 years mindi wood was 55–85 oC; for 9 years was 50–80 oC; and for 5 years was 40–65 oC. Supported by the performance of wood surface, especially at 13 years old, mindi wood was suitable for wooden furniture.